2016
DOI: 10.1016/j.actatropica.2016.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Dengue virus surveillance: Detection of DENV-4 in the city of São José do Rio Preto, SP, Brazil

Abstract: Dengue viruses are the most common arbovirus infection worldwide and are caused by four distinct serotypes of the dengue virus (DENV). In the present study, we assessed DENV transmission in São José do Rio Preto (SJRP) from 2010 to 2014. We analyzed blood samples from febrile patients who were attended at health care centers in SJRP. DENV detection was performed using multiplex RT-PCR, using flavivirus generic primers, based on the genes of the non-structural protein (NS5), followed by nested-PCR assay with sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 52 publications
(63 reference statements)
0
8
0
Order By: Relevance
“…All ZIKV positive animals were negative for YFV in RT-qPCR and RT-nested-PCR and a subset that was tested by immunohistochemistry to YFV exposure, were also negative. Our results demonstrated that free-living marmosets and capuchin monkeys may be naturally infected with ZIKV in urban areas of Southeast Brazil (São Paulo and Minas Gerais States), regions of intense arboviral circulation 26 32 . A previous study demonstrated ZIKV RNA detection in sera and/or oral swabs (not further specified in prior studies) from free-living common marmosets (n = 4) and capuchin monkeys (n = 3), in Northeast Brazil 8 .…”
Section: Discussionmentioning
confidence: 65%
“…All ZIKV positive animals were negative for YFV in RT-qPCR and RT-nested-PCR and a subset that was tested by immunohistochemistry to YFV exposure, were also negative. Our results demonstrated that free-living marmosets and capuchin monkeys may be naturally infected with ZIKV in urban areas of Southeast Brazil (São Paulo and Minas Gerais States), regions of intense arboviral circulation 26 32 . A previous study demonstrated ZIKV RNA detection in sera and/or oral swabs (not further specified in prior studies) from free-living common marmosets (n = 4) and capuchin monkeys (n = 3), in Northeast Brazil 8 .…”
Section: Discussionmentioning
confidence: 65%
“…Our results suggest that NAF identifies areas of higher risk of dengue occurrence. Additionally, NAF may serve as a new surveillance and control tool to detect and restrain The validation of NAF as an index to measure risk of disease occurred simultaneously with the introduction of DENV-4 in São José do Rio Preto (Colombo et al, 2016;Rocco et al, 2012). DENV-4 was the only serotype detected in our mosquitoes, which is an indication this was the main serotype causing dengue fever, at least in the study area.…”
Section: Discussionmentioning
confidence: 80%
“…Since 2006, we have established arbovirus surveillance for encephalitis-suggestive cases in the city of São José do Rio Preto (SJdRP), State of São Paulo, Brazil, located in a hyper-endemic area for dengue virus (DENV) [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ], Saint Louis encephalitis [ 40 , 41 ], Zika virus (ZIKV) [ 34 ], and documented co-infection among various flaviviruses [ 30 , 41 , 42 ]. Herein, we report a case of cerebral encephalitis in a patient infected with ILHV that was observed by our surveillance team in São José do Rio Preto (SJdRP).…”
Section: Introductionmentioning
confidence: 99%